Laminate film
By using a multi-layer structure and a layer composed of specific resins on the polymer film, the problems of optical interference chromatic aberration and low reflection are solved, and a low-reflection surface without interference chromatic aberration under polarization conditions is achieved, which is suitable for the surface protection film of the display.
Patent Information
- Application Number
- JP2023165219
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is still not sufficient when reducing the chromatic aberration problems caused by optical interference, especially at the tilted viewing angle, and it is difficult to achieve both low reflection (anti-glare) and low-light interference (reduced interference texture) effects on the surface.
A polymer film with a multi-layer structure is adopted, wherein the retardation (Re) of one polymer film is less than 3000 nm, and the layer contained on the surface is a layer composed of a specific resin, including metal oxide particles with high reflectivity and resin with a condensed polycyclic aromatic structure.
It realizes a low-reflection surface without optical interference chromatic aberration under polarization conditions, while maintaining high transparency and low interference texture effects, and is suitable for the surface protection film of the display.
Smart Images

Figure 2025055836000003 
Figure 2025055836000004 
Figure 2025055836000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated film having excellent low reflection characteristics (antiglare properties) and low optical interference (suppression of occurrence of interference fringes). [Background technology]
[0002] 2. Description of the Related Art Polyester films have traditionally been used widely as materials for various applications, such as magnetic tapes, ferromagnetic thin film tapes, photographs, packaging, electronic components, electrical insulation, and metal laminates, due to their excellent mechanical properties and chemical resistance. In recent years, they have been increasingly used in various optical films, such as prism sheets, light diffusion sheets, reflectors, base films for touch panels, anti-reflection base films, and OLED components.
[0003] In the above optical products, in order to obtain clear images, the optical film must have good transparency and be free of defects such as foreign matter and scratches that affect the image. In particular, in the application of polarizer protective films, which are components of polarizing plates, the replacement of conventional TAC (triacetyl cellulose) films with biaxially stretched polyester films is being considered for the purpose of reducing costs. Biaxially stretched polyester films have a problem in that interference colors occur due to optical interference under polarized light due to anisotropy during stretching. To solve this problem, for example, measures have been taken to control the retardation within a specific range. (Patent Documents 1 and 2) [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-200435 A [Patent Document 2] JP 2013-200578 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, although Patent Documents 1 and 2 have an improvement effect on the occurrence of interference colors due to optical interference, depending on the angle at which the display is viewed, for example, when viewed from an oblique direction, there are cases in which the occurrence of interference colors due to optical interference is insufficient to be reduced, and further improvement is anticipated. Furthermore, there are types of protective film that require low reflection characteristics (anti-glare properties) on the surface, and there was a situation where it was necessary to achieve both low reflection characteristics (anti-glare properties) and low optical interference (suppression of the occurrence of interference fringes).
[0006] The present invention has been made in consideration of the above-mentioned circumstances, and the problem to be solved by the present invention is to provide a laminated film that can be used as a surface protection film for a display, for example, under polarized light, without generating interference colors due to optical interference, and yet has low reflection characteristics (anti-glare properties). [Means for solving the problem]
[0007] In view of the above circumstances, the present inventors have conducted intensive research and found that the above problems can be easily solved by providing a film with a resin layer having a specific composition, and have completed the present invention. That is, the present invention provides the following items [1] to
[20] .
[0008] [1] A laminate film having a structure in which a resin layer A and a resin layer C are laminated in this order on one surface of a polyester film, and a resin layer B is laminated on the opposite surface, the polyester film has a retardation (Re) of less than 3000 nm, the resin layer A is a cured product of a resin composition A containing (a) a binder, (b) a crosslinking agent, and (c) particles, the resin layer C is a cured product of a resin composition C containing (X) a (meth)acrylate and (Y) inorganic oxide fine particles having an average particle size of 0.1 to 5 μm, and the (a) binder contains a compound having a condensed polycyclic aromatic structure. [2] The laminate film according to the above [1], wherein the average reflectance of the surface of the resin layer C at a wavelength of 380 to 760 nm is 3.0% or less. [3] The laminate film according to the above [1] or [2], wherein the compound having a condensed polycyclic aromatic structure is a polycyclic polyester resin. [4] The laminate film according to any one of the above [1] to [3], having a film haze of 1.5% or less. [5] The laminate film according to any one of the above [1] to [4], wherein the polyester film contains an ultraviolet absorber. [6] The laminated film according to any one of the above [1] to [5], wherein the polyester film is a polyethylene terephthalate (PET) film. [7] The laminated film according to any one of the above [1] to [6], wherein the refractive index difference (nx-ny) of the polyester film is 0.04 or less. [8] The laminate film according to any one of the above [1] to [7], wherein the polyester film has a thickness of 9 to 125 μm. [9] The laminate film according to any one of the above [1] to [8], wherein the resin layer A has a thickness of 10 to 60 nm.
[10] The laminate film according to any one of the above [1] to [9], wherein the resin layer B has a thickness of 20 to 100 nm.
[11] The laminate film according to any one of the above [1] to
[10] , wherein the resin layer C has a thickness of 10 μm or less.
[12] The laminate film according to any one of the above [1] to
[11] , having a structure of backlight (light source) / polarizing plate 0° / polarizing plate 45° / laminate film, in which the resin layer C side of the laminate film is not in contact with the 45° polarizing plate, and when the appearance is evaluated from the resin layer C side, the area of coloring (rainbow unevenness) is 30% or less of the entire measured area.
[13] The laminate film according to any one of the above [1] to
[12] , having a structure of backlight (light source) / polarizing plate 0° / polarizing plate 90° / laminate film, in which the resin layer C side of the laminate film is not in contact with the 90° polarizing plate, and when the appearance is evaluated from the resin layer C side, the area of coloring (rainbow unevenness) is 50% or less of the entire measured area.
[14] A method for producing a laminated film according to any one of the above [1] to
[11] , comprising: a production step 1 of stretching the film in the longitudinal direction by 3.0 to 4.0 times, coating one side of the longitudinally stretched film with a coating solution of resin composition A and resin composition B, introducing the film into a tenter, stretching the film in the transverse direction by 3.6 to 6.0 times, and heat-treating the film at 215°C or less to obtain a laminated polyester film having a resin layer A on one side and a resin layer B on the other side; and a production step 2 of coating resin composition C on the resin layer A side of the laminated polyester film and drying the film.
[15] The laminate film according to any one of the above [1] to
[13] , which is for surface protection.
[16] The laminate film according to any one of the above [1] to
[13] , which is used for protecting a display surface.
[17] The laminate film according to any one of the above [1] to
[13] , which is for protecting a polarizer.
[18] A polarizing plate comprising the laminate film according to any one of the above [1] to
[13] , and the resin layer B attached to one side of a polarizer.
[19] An image display device comprising the polarizing plate according to
[18] above.
[20] The image display device according to
[19] above, which is for mounting on a vehicle. Effect of the Invention
[0009] According to the present invention, it is possible to provide a laminate film that can be used as a surface protection film for a display, for example, under polarized light, without generating interference colors due to optical interference, and yet has low reflection properties (anti-glare properties). [Brief description of the drawings]
[0010] [Figure 1] 1 is a photograph showing the state of optical coherence (interference fringes) in Example 1 (interference fringe I evaluation). [Diagram 2] 1 is a photograph showing the state of optical coherence (interference fringes) in Example 2 (interference fringes I evaluation). [Diagram 3] 1 is a photograph showing the state of optical coherence (interference fringes) in Comparative Example 1 (evaluation of interference fringes I). [Figure 4] 1 is a configuration example of a laminated film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Next, the present invention will be described based on an embodiment, however, the present invention is not limited to the embodiment described below.
[0012] <<Laminated film>> A laminate film according to one embodiment of the present invention (hereinafter, referred to as "the present laminate film") will be described below with reference to FIG. This laminate film 1 is a laminate film having a configuration in which a resin layer A (4 in Figure 4) and a resin layer C (5 in Figure 4) are laminated in that order on one surface of a polyester film 3, and a resin layer B (2 in Figure 4) is laminated on the opposite surface. As long as the present laminate film has the above-mentioned structure, it may have other layers.
[0013] <Polyester film> The polyester film may be a single layer or a multilayer, and the main component resin of each layer is preferably polyester. In this specification, such a film is called a "polyester film". Here, the "main component resin" means the resin that is contained in the film at the highest ratio, and is a resin that occupies 50% by mass or more, particularly 70% by mass or more, and of these, 80% by mass or more (including 100% by mass) of the resins that constitute the polyester film. Each layer constituting the polyester film may contain a resin other than polyester or a component other than resin, so long as the main component resin is polyester. When the polyester film has a multi-layer structure, it may have not only a two-layer or three-layer structure but also a four-layer or more layer structure as long as it does not deviate from the gist of the present invention.
[0014] (polyester) The polyester (hereinafter referred to as "the polyester") used as the main component resin of each layer constituting the polyester film may be either a homopolyester or a copolymer polyester.
[0015] When the present polyester is a homopolyester, it is preferably one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid. Examples of the aliphatic glycol include ethylene glycol, diethylene glycol, and 1,4-cyclohexanedimethanol.
[0016] When the polyester is a copolymer polyester, the dicarboxylic acid component may be, for example, one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, sebacic acid, etc. On the other hand, the glycol component may be, for example, one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, etc.
[0017] As the polymerization catalyst for polyester, known catalysts such as antimony compounds, germanium compounds, titanium compounds, aluminum compounds, etc. can be used. Among these, in the present invention, polyesters polymerized using antimony compounds or titanium compounds as catalysts are preferred. Specific examples of typical polyesters include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polybutylene naphthalate (PBN), polyethylene furanoate (PEF), etc. Among them, PET and PEN are preferable from the viewpoint of handling, and PET is most preferable. In addition, when the main component resin of each layer constituting the polyester film is, for example, polyethylene terephthalate, the film is called a “polyethylene terephthalate film.” The same applies when the main component resin is another resin.
[0018] (Other resin components) Each layer constituting the polyester film may contain a resin other than polyester, such as epoxy, polyarylate, polyethersulfone, polycarbonate, polyetherketone, polysulfone, polyphenylene sulfide, polyester-based liquid crystal polymer, triacetyl cellulose, cellulose derivatives, polypropylene, polyamides, polycycloolefins, etc.
[0019] (particle) The film may contain particles mainly for the purposes of imparting lubricity to the film surface and preventing scratches during each process. The type of the particles is not particularly limited as long as they are particles that can provide easy slipping. For example, inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin can be mentioned. These can be used alone or in combination of two or more kinds. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process can also be used.
[0020] The shape of the particles is not particularly limited, and may be, for example, spherical, blocky, rod-like, flat, or the like. Furthermore, there is no particular restriction on the hardness, specific gravity, color, etc. of the above particles. Two or more kinds of these particles may be used in combination as necessary.
[0021] The average particle size of the particles is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 2.5 μm or less. If it is 5 μm or less, the surface roughness of the polyester film is not too rough, and no problems occur when forming a cured resin layer made of various curing compositions in a later process. On the other hand, the average particle size of the particles is preferably 0.01 μm or more, and even more preferably 0.5 μm or more.
[0022] The particle content in the polyester film is preferably 5% by mass or less, more preferably from 0.0003% to 3% by mass, and even more preferably from 0.01% to 2% by mass. When the average particle size of the particles is within the above range, the surface roughness of the polyester film is not too rough, and problems that arise when forming a cured resin layer made of various curing compositions in a subsequent process can be suppressed.
[0023] The method of adding particles to the polyester film is not particularly limited, and any conventionally known method can be used. For example, the particles can be added at any stage of the production of raw material resin such as polyester. It is preferable to add the particles after the completion of esterification or transesterification reaction.
[0024] (Other ingredients) The polyester film may contain other components, as required, such as conventionally known antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, and ultraviolet absorbing agents. In particular, it is preferred that the laminate film contains an ultraviolet absorbing agent in order to ensure the weather resistance of the film.
[0025] (Thickness) The thickness of the polyester film is, for example, preferably 9 to 125 μm, more preferably 12 to 100 μm, and even more preferably 20 to 75 μm, in order to obtain necessary and sufficient rigidity and handleability.
[0026] (Production method) The polyester film can be formed, for example, from a resin composition by a melt casting method or a solution casting method. In the case of a multi-layer structure, co-extrusion may be used. The film may be uniaxially or biaxially stretched, with the biaxially stretched film being preferred from the standpoint of rigidity.
[0027] In general, first, undried or dried polyester chips are fed into a melt extrusion device by a known method, and heated to a temperature equal to or higher than the melting point of each polymer to melt it. The molten polymer is then extruded from a die and rapidly cooled to a temperature equal to or lower than the glass transition temperature on a rotating cooling drum to obtain a substantially amorphous unoriented sheet. In this case, in order to improve the flatness of the sheet, it is preferable to increase the adhesion between the sheet and the rotating cooling drum, and in the present invention, an electrostatic application adhesion method and / or a liquid application adhesion method are preferably adopted.
[0028] From the viewpoint of film strength, it is preferable to biaxially stretch the unoriented sheet obtained as described above to form a film. Specifically, the stretching conditions are that the unoriented sheet (unstretched sheet) is stretched in the longitudinal direction (machine direction) at 70 to 145°C, preferably 80 to 120°C, at a stretch ratio of 2.0 to 4.5 times, preferably 3.0 to 4.0 times, to form a uniaxially stretched film. Next, the film is stretched in the transverse direction (width direction) perpendicular to the longitudinal direction (machine direction) at a stretching ratio of 3.0 to 6.5 times or 3.5 to 6.0 times at 90 to 160° C. to obtain a biaxially stretched film. Subsequently, it is preferable to perform a heat treatment (heat setting) for 10 to 600 seconds under tension or relaxation of 30% or less at 200 to 260° C. Among them, a method of relaxing by 1 to 10% in the longitudinal and / or transverse directions at 200 to 230° C. in the maximum temperature zone of the heat treatment and / or in the cooling zone at the exit of the heat treatment is preferable. The longitudinal direction (machine direction) of the film refers to the direction in which the film advances during the film manufacturing process, i.e., the direction in which the film roll is wound. The transverse direction (width direction) refers to the direction parallel to the film surface and perpendicular to the longitudinal direction, i.e., the direction parallel to the central axis of the roll when the film is in a roll shape.
[0029] In particular, when the film is used for applications requiring low retardation (hereinafter sometimes referred to as "Re") as in the present invention, it is preferable that the difference between the longitudinal and transverse stretching ratios is small, and is 0.5 times or less, and more preferably 0.3 times or less. The heat treatment temperature is also preferably low, and is preferably 210°C or less, more preferably 200°C or less, and even more preferably 180°C or less. By satisfying the above range, a polyester film having a Re of a certain level or less can be obtained, regardless of the sampling position in the width direction of the film.
[0030] The refractive index difference (nx-ny) of the polyester film is preferably 0.04 or less. By satisfying the above range, it is possible to contribute to reducing the occurrence of rainbow unevenness when used in combination with various light sources. From the above viewpoint, the refractive index difference (nx-ny) of the polyester film can be adjusted to 0.04 or less by setting the difference between the stretching ratios in the longitudinal direction and the transverse direction to 0.5 times or less, more preferably 0.3 times or less. Here, nx is the refractive index in the slow axis direction in the plane of the polyester film (the direction showing the maximum refractive index in the film plane), and ny is the refractive index in the fast axis direction in the plane of the polyester film (the direction perpendicular to nx in the film plane).
[0031] (Re(retardation)) The polyester film must have a retardation (Re) of less than 3000 nm. If the retardation is less than 3000 nm, interference fringes can be suppressed. From the above viewpoint, the retardation is preferably 2000 nm or less, more preferably 1500 nm or less, and particularly preferably 1000 nm or less. The retardation can be measured by the method described in the examples. The change in retardation (Re) in the width direction is preferably from 10 nm / m to 600 nm / m, more preferably from 15 nm / m to 550 nm / m, and even more preferably from 20 nm / m to 550 nm / m. Here, the change in the widthwise retardation (Re) is calculated by calculating the difference between the maximum and minimum retardation values obtained from each film sample, and dividing this difference by the distance (m) in the widthwise direction between the positions on the film sample where the maximum and minimum values were obtained. Furthermore, the area of the Re range is preferably 50% or more of the entire area in the width direction of the film, more preferably 55% or more, and even more preferably 60% or more. In particular, if the area in the range where the retardation (Re) in the width direction is 10 to 550 nm / m is 50% or more, preferably 60% or more, and more preferably 70% or more of the entire area in the width direction of the film, then in a wide film compatible with a large-screen display of, for example, 40 inches or more, preferably 50 inches or more, the fluctuation range of the retardation within the film plane is small, and it is possible to reduce the occurrence of rainbow unevenness when used in combination with various light sources.
[0032] <Resin layer A, resin layer B, and resin layer C> The laminated film has a laminated structure in which a resin layer A and a resin layer C are provided in this order on one side of a polyester film, and a resin layer B is provided on the opposite side. The resin layer C is a cured product of a resin composition C containing (X) a urethane (meth)acrylate and (Y) inorganic oxide particles having an average particle size of 0.1 to 5 μm.
[0033] The thickness of the resin layer C is preferably 10 μm or less, more preferably 1.0 μm or more and 10.0 μm or less, more preferably 1.0 μm or more and 8.0 μm or less, even more preferably 1.0 μm or more and 6.0 μm or less, and particularly preferably 1.0 μm or more and 5.0 μm or less.
[0034] The surface of the resin layer C preferably has a light transmittance of 3.0% or less at a wavelength of 380 nm. A light transmittance of 3.0% or less is advantageous in that the mating member to be bonded can be prevented from being deteriorated by ultraviolet rays. From the above viewpoint, the light transmittance of 2.8% or less at a wavelength of 380 nm is more preferable.
[0035] In addition, the average reflectance of the surface of the resin layer C at wavelengths of 380 to 780 nm is preferably 3.0% or less. If the average reflectance is 3.0% or less, light is less likely to be reflected, which is advantageous in that the antiglare properties are good. From the above viewpoints, the average reflectance is more preferably 2.5% or less.
[0036] (Surface condition of each layer) The surfaces of the resin layer A and the resin layer B may be uneven or flat, but from the viewpoint of appearance (surface gloss), it is preferable that they are flat. From the viewpoint of imparting antiglare properties, the surface of the resin layer C is preferably uneven. This can be arbitrarily selected according to the required properties.
[0037] <<Laminated film manufacturing method>> Each of the resin layers A, B, and C can be formed by curing a curable resin composition, i.e., a resin composition having a curable property (hereinafter, sometimes referred to as "resin composition"). That is, the resin layer is formed by applying a resin composition having a mass average molecular weight in the range of 1,000 to 500,000 onto a polyester film and curing the composition. The resin composition for forming the resin layer A is referred to as resin composition A, the resin composition for forming the resin layer B is referred to as resin composition B, and the resin composition for forming the resin layer C is referred to as resin composition C. More specifically, the present laminate film can be produced by coating one surface of a polyester film with resin composition A and curing it to form resin layer A, coating the opposite surface with resin composition B and curing it to form resin layer B, and then coating resin composition C on resin layer A and curing it to form resin layer C. In this case, resin layer A and resin layer B may be cured simultaneously. In addition, after forming the resin layer A and the resin layer B, the film may be temporarily wound into a roll and then unwound again, and the resin composition C may be applied onto the resin layer A and cured to form the resin layer C. In addition, after forming the resin layer A on the surface of the polyester film, the resin composition C may be continuously applied and cured to form the resin layer C, and then the resin composition B may be applied onto the opposite surface and cured to form the resin layer B. The method for producing the laminated film is not limited to such a method.
[0038] The method for producing the laminated film of the present invention will be described in detail. The method for producing the laminated film of the present invention preferably includes the following production steps 1 and 2. First, an unoriented sheet is obtained as described in the above-mentioned polyester film production method. Next, in production step 1, the unoriented sheet is stretched in the longitudinal direction by 3.0 to 4.0 times, and then coating solutions of resin composition A and resin composition B described below are applied to both sides of one side of the longitudinally stretched film, which is introduced into a tenter and stretched in the transverse direction by 3.6 to 6.0 times, and heat-treated at 215°C or less to obtain a laminated polyester film having a resin layer A on one side and a resin layer B on the opposite side. Next, in production step 2, the method includes a step of applying resin composition C onto the resin layer A side of the laminated polyester film and drying it.
[0039] <Resin composition> Resin composition A, resin composition B and resin composition C for forming resin layer A, resin layer B and resin layer C will be described below.
[0040] (Resin Composition A) The resin composition A includes (a) a binder, (b) a crosslinking agent, and (c) particles, which will be described in detail below.
[0041] (a) Binder The binder used in the resin composition (a) is preferably a resin, and examples of the resin constituting the binder include polyester resin, acrylic resin, and urethane resin.
[0042] (polyester resin) The polyester resin is composed of, for example, the following polyvalent carboxylic acid and polyvalent hydroxy compound as main components. That is, as the polyvalent carboxylic acid, terephthalic acid, isophthalic acid, orthophthalic acid, 4,4'-diphenyldicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfoisophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof can be used, and as the polyvalent hydroxy compound, Ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, sodium dimethylolethylsulfonate, potassium dimethylolpropionate, etc. can be used. One or more of these compounds can be appropriately selected from each of them, and a polyester resin can be synthesized by a conventional polycondensation reaction.
[0043] (Acrylic resin) The acrylic resin is not particularly limited and may be appropriately selected within a range in which the effects of the present invention can be achieved. For example, (meth)acrylate is preferred. Examples of the monofunctional (meth)acrylate include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate; and hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutyl hydroxyl fumarate, and monobutyl hydroxy itaconate. Examples of bifunctional (meth)acrylates include alkanediol di(meth)acrylates such as 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and tricyclodecanedimethylol di(meth)acrylate; bisphenol-modified di(meth)acrylates such as bisphenol A ethylene oxide-modified di(meth)acrylate and bisphenol F ethylene oxide-modified di(meth)acrylate; polyethylene glycol di(meth)acrylate; polypropylene glycol di(meth)acrylate; urethane di(meth)acrylate; and epoxy di(meth)acrylate.
[0044] Examples of the trifunctional or higher polyfunctional (meth)acrylate include ethylene oxide-modified (meth)acrylates such as dipentaerythritol hexa(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate and ethylene oxide-modified pentaerythritol tetra(meth)acrylate, isocyanuric acid-modified tri(meth)acrylate, and ε-caprolactone-modified tris(acryloxyethyl)isocyanurate. Further, there may be mentioned (meth)acrylates having an epoxy group, such as glycidyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, etc. Among these, in consideration of good reactivity and ease of use of the material, glycidyl (meth)acrylate is preferred, and glycidyl methacrylate is particularly preferred. Further preferred examples include carboxy group-containing (meth)acrylates such as acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, citraconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0045] (urethane resin) A urethane resin is a polymeric compound having a urethane structure in the molecule. Usually, a urethane resin is produced by the reaction of a polyol with a polyisocyanate. Examples of polyols include polycarbonate polyols, polyester polyols, polyether polyols, polyolefin polyols, and acrylic polyols. These compounds may be used alone or in combination.
[0046] Polycarbonate polyols are obtained by dealcoholization reaction between polyhydric alcohols and carbonate compounds. Examples of polyhydric alcohols include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, and 3,3-dimethylolheptane. Examples of carbonate compounds include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, etc., and examples of polycarbonate-based polyols obtained by the reaction of these compounds include poly(1,6-hexylene) carbonate, poly(3-methyl-1,5-pentylene) carbonate, etc.
[0047] Examples of polyester polyols include polycarboxylic acids (malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, isophthalic acid, etc.) or their acid anhydrides and polyhydric alcohols (ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl-2 ,4-pentanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamines, lactonediols, etc.
[0048] Examples of polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol.
[0049] Examples of polyisocyanate compounds used to obtain urethane resins include aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and tolidine diisocyanate, aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethyl xylylene diisocyanate, aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate, and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidenedicyclohexyl diisocyanate. These may be used alone or in combination.
[0050] A chain extender may be used when synthesizing the urethane resin, and the chain extender is not particularly limited as long as it has two or more active groups that react with the isocyanate group. In general, a chain extender having two hydroxyl groups or two amino groups can be mainly used.
[0051] Examples of chain extenders having two hydroxyl groups include glycols such as aliphatic glycols, such as ethylene glycol, propylene glycol, and butanediol; aromatic glycols, such as xylylene glycol and bishydroxyethoxybenzene; and ester glycols, such as neopentyl glycol hydroxypivalate. Examples of chain extenders having two amino groups include aromatic diamines such as tolylenediamine, xylylenediamine, and diphenylmethanediamine; aliphatic diamines such as ethylenediamine, propylenediamine, hexanediamine, 2,2-dimethyl-1,3-propanediamine, 2-methyl-1,5-pentanediamine, trimethylhexanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine; and alicyclic diamines such as 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, dicyclohexylmethanediamine, isopropylidincyclohexyl-4,4'-diamine, 1,4-diaminocyclohexane, and 1,3-bisaminomethylcyclohexane.
[0052] In the laminate film of the present invention, it is essential that the binder (a) contains a compound having a condensed polycyclic aromatic structure. By containing such a compound, the refractive index of the resin layer A can be easily adjusted.
[0053] Examples of compounds having a condensed polycyclic aromatic structure include naphthalene, anthracene, phenanthrene, naphthacene, benzo[a]anthracene, benzo[a]phenanthrene, pyrene, benzo[c]phenanthrene, and perylene, as exemplified by the following formulas.
[0054] [ka]
[0055] Considering the coatability onto a polyester film, the compound having a condensed polycyclic aromatic group is preferably a polymer compound such as a polycyclic polyester resin, etc. In particular, polycyclic polyester resins are more preferred because they can introduce a larger number of condensed polycyclic aromatic groups.
[0056] Methods for incorporating a condensed polycyclic aromatic compound into a polyester resin include, for example, introducing two or more hydroxyl groups as substituents into the condensed polycyclic aromatic compound to prepare a diol component or a polyvalent hydroxyl group component, or introducing two or more carboxylic acid groups to prepare a dicarboxylic acid component or a polyvalent carboxylic acid component.
[0057] In the laminated polyester film manufacturing process, the condensed polycyclic aromatic compound contained in the resin layer A is preferably a compound having a naphthalene skeleton, since it is less likely to be discolored. In addition, a resin incorporating a naphthalene skeleton is preferably used as a polyester constituent, since it has good adhesion to the resin layer C formed on the resin layer A and good transparency. Representative examples of the naphthalene skeleton include 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid.
[0058] In the compound having a condensed polycyclic aromatic group, the proportion of the condensed polycyclic aromatic ring in the compound is preferably in the range of 5 to 80 mass%, more preferably 10 to 60 mass%. For example, in the case of a polyester resin having a naphthalene ring as the condensed polycyclic aromatic group, this means the content of the naphthalene ring in the polyester resin. In addition, the content of the compound having a condensed polycyclic aromatic in the resin composition A is preferably 80% by mass or less, more preferably 5 to 70% by mass, and particularly preferably 10 to 50% by mass. By satisfying the above range, it becomes easy to adjust the refractive index of the resin layer A itself, and it becomes easy to reduce interference unevenness after forming the cured resin layer (B). The proportion of the condensed polycyclic aromatic can be determined, for example, by dissolving and extracting the coating layer with an appropriate solvent or warm water, separating it by chromatography, analyzing the structure by NMR or IR, and further analyzing it by pyrolysis GC-MS (gas chromatography mass spectrometry) or optical analysis.
[0059] In addition to hydroxyl groups and carboxylic acid groups, introduction of a substituent containing elemental sulfur, an aromatic substituent such as a phenyl group, or a halogen group into the condensed polycyclic aromatic compound is expected to improve the refractive index, and from the viewpoint of coatability and adhesion, a substituent such as an alkyl group, an ester group, an amide group, a sulfonic acid group, a carboxylic acid group, or a hydroxyl group may be introduced.
[0060] The content of the (a) binder in the resin composition A is usually 1 to 60 mass %, preferably 3 to 40 mass %, and more preferably 5 to 25 mass %. By satisfying this range, good image film properties can be ensured.
[0061] (b) Crosslinking agent Examples of the crosslinking agent include oxazoline compounds, melamine compounds, epoxy compounds, carbodiimide compounds, and isocyanate compounds.
[0062] (Oxazoline compounds) The oxazoline compound is a compound having an oxazoline group in the molecule, and a polymer containing an oxazoline group is particularly preferred. The oxazoline compound can be prepared by polymerization of an addition polymerizable oxazoline group-containing monomer alone or with other monomers. Examples of the addition polymerizable oxazoline group-containing monomer include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline, and one or a mixture of two or more of these can be used. Among these, 2-isopropenyl-2-oxazoline is suitable because it is easily available industrially. The other monomer is not limited as long as it is a monomer that can be copolymerized with the addition-polymerizable oxazoline group-containing monomer, and examples thereof include (meth)acrylic acid esters such as alkyl (meth)acrylates (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrenesulfonic acid, and salts thereof (sodium salts, potassium salts, ammonium salts, tertiary amine salts, and the like); unsaturated nitriles such as acrylonitrile and methacrylonitrile; (meth)acrylamide, N-alkyl (meth)acrylamide, and the like. Examples of the monomers that can be used include unsaturated amides such as N,N-dialkyl(meth)acrylamide (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride, vinylidene chloride, and vinyl fluoride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. One or more of these monomers can be used.
[0063] (Melamine compounds) The melamine compound is a compound having a melamine skeleton in the compound. For example, an alkylolated melamine derivative, a compound partially or completely etherified by reacting an alkylolated melamine derivative with an alcohol, and a mixture of these can be used. As the alcohol used for etherification, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-butanol, isobutanol, etc. are preferably used. In addition, the melamine compound may be either a monomer or a dimer or higher polymer, or a mixture of these may be used. Furthermore, a product obtained by co-condensing a part of melamine with urea or the like can also be used, and a catalyst can also be used to increase the reactivity of the melamine compound.
[0064] (Epoxy compounds) An epoxy compound is a compound having an epoxy group in the molecule, and examples thereof include condensation products of epichlorohydrin with hydroxyl groups or amino groups of ethylene glycol, polyethylene glycol, glycerin, polyglycerin, bisphenol A, etc., polyepoxy compounds, diepoxy compounds, monoepoxy compounds, glycidylamine compounds, etc. Examples of polyepoxy compounds include sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, and examples of diepoxy compounds include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol ... Examples of monoepoxy compounds include allyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether. Examples of glycidyl amine compounds include N,N,N',N'-tetraglycidyl-m-xylylenediamine and 1,3-bis(N,N-diglycidylamino)cyclohexane.
[0065] (Carbodiimide compounds) A carbodiimide compound is a compound having a carbodiimide structure, and is a compound having one or more carbodiimide structures in the molecule. For better adhesion, etc., a polycarbodiimide compound having two or more carbodiimide structures in the molecule is more preferred.
[0066] Carbodiimide compounds can be synthesized by conventionally known techniques, and generally, condensation reaction of diisocyanate compounds is used.Diisocyanate compounds are not particularly limited, and both aromatic and aliphatic compounds can be used, and specific examples include tolylene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, dicyclohexylmethane diisocyanate, etc.
[0067] Furthermore, in order to improve the water solubility or water dispersibility of the polycarbodiimide-based compound, a surfactant may be added, or a hydrophilic monomer such as a polyalkylene oxide, a quaternary ammonium salt of a dialkylamino alcohol, or a hydroxyalkylsulfonate may be added, within a range that does not impair the effects of the present invention.
[0068] (Isocyanate compounds) The isocyanate compound is a compound having an isocyanate or an isocyanate derivative structure, such as a blocked isocyanate. Examples of the isocyanate include aromatic isocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate, aliphatic isocyanates having an aromatic ring such as α,α,α',α'-tetramethyl xylylene diisocyanate, aliphatic isocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate, and alicyclic isocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isopropylidenedicyclohexyl diisocyanate. In addition, polymers and derivatives such as biuretized products, isocyanurate products, uretdione products, and carbodiimide modified products of these isocyanates are also included. These may be used alone or in combination. Among the above isocyanates, aliphatic isocyanates or alicyclic isocyanates are more preferable than aromatic isocyanates in order to prevent yellowing due to ultraviolet rays.
[0069] When used in the form of a blocked isocyanate, examples of the blocking agent include bisulfites, phenolic compounds such as phenol, cresol, and ethylphenol, alcohol compounds such as propylene glycol monomethyl ether, ethylene glycol, benzyl alcohol, methanol, and ethanol, active methylene compounds such as dimethyl malonate, diethyl malonate, methyl acetoacetate, ethyl acetoacetate, and acetylacetone, mercaptan compounds such as butyl mercaptan and dodecyl mercaptan, lactam compounds such as ε-caprolactam and δ-valerolactam, amine compounds such as diphenylaniline, aniline, and ethyleneimine, acetanilide, acid amide compounds of acetic acid amide, and oxime compounds such as formaldehyde, acetaldoxime, acetoneoxime, methyl ethyl ketoneoxime, and cyclohexanoneoxime, which may be used alone or in combination of two or more.
[0070] The content of the (b) crosslinking agent in the resin composition A is usually 2 to 80 mass %, preferably 4 to 60 mass %, and more preferably 10 to 40 mass %. By satisfying this range, the adhesion to the resin layer C becomes good.
[0071] (c) Particles From the viewpoint of imparting a high refractive index to the resin layer A, it is preferable that the resin composition A contains metal oxide particles. By increasing the refractive index, interference fringes can be suppressed. (Metal oxides) It is preferable to use a metal oxide having a high refractive index, and it is preferable to use one having a refractive index of 1.7 or more.Specific examples of metal oxides include zirconium oxide, titanium oxide, tin oxide, yttrium oxide, antimony oxide, indium oxide, zinc oxide, antimony tin oxide, indium tin oxide, etc., and these may be used alone or in combination of two or more.Among these, zirconium oxide and titanium oxide are more preferably used, and zirconium oxide is more preferably used in terms of weather resistance.
[0072] Metal oxides are preferably used in the form of particles since there is a concern that their adhesion may decrease depending on the form of use, and the average particle size is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 25 nm or less from the viewpoint of transparency. The lower limit of the average particle size is not particularly limited, but is preferably 5 nm or more, and more preferably 10 nm or more, from the viewpoint of dispersibility.
[0073] In addition, the resin composition A may contain particles other than the above-mentioned metal oxides for the purpose of improving adhesion and slippage. The average particle size is preferably 1.0 μm or less from the viewpoint of film transparency, more preferably 0.5 μm or less, and particularly preferably 0.2 μm or less. The lower limit of the average particle size is not particularly limited, but is preferably 5 nm or more from the viewpoint of dispersibility, and more preferably 10 nm or more. Specific examples of particles include silica, alumina, kaolin, calcium carbonate, organic particles, and the like. In addition, it is preferable to use two types of particles having different particle sizes in terms of imparting lubricity.
[0074] The proportion of the (c) particles relative to the total non-volatile components in the resin composition A forming the resin layer A is usually 3 to 70 mass%, preferably 5 to 50 mass%, more preferably 5 to 40 mass%, and particularly preferably 8 to 30 mass%. By satisfying the above range, it is possible to achieve both transparency and low interference effect of the film. In particular, a combination of particles of a metal compound or the like and the above-mentioned polycyclic polyester resin provides a more excellent effect of reducing interference.
[0075] (Thickness) The thickness of the resin layer A is in the range of 10 to 60 nm, preferably 20 to 60 nm, and more preferably 20 to 40 nm. By setting the thickness of the resin layer A in the above range, good antiglare properties can be achieved in combination with the resin layer C.
[0076] (Refractive Index) The refractive index of the resin layer A is in the range of 1.60 to 1.69, preferably 1.60 to 1.66. By setting the refractive index of the resin layer A in the above range, in combination with the resin layer C, good antiglare properties can be achieved.
[0077] (Resin composition B) Resin composition B preferably contains (a) a binder, (b) a crosslinking agent, and (c) particles. In order to keep the reflectance low after laminating resin layer C, it is preferable that resin layer B has a smaller refractive index than resin layer A. From that viewpoint, in resin composition B, as described above, the same materials as resin composition A can be used as long as a material that increases the refractive index is not used.
[0078] (Thickness) The thickness of the resin layer B is preferably in the range of 20 to 100 nm, more preferably 40 to 80 nm, and further preferably 40 to 60 nm. By setting the thickness of the resin layer B in the above range, for example, when the present laminate film is bonded to a polarizer, good adhesion to the adhesive layer on the polarizer side can be ensured.
[0079] (Refractive Index) The refractive index of the resin layer B is preferably in the range of 1.50 to 1.60, and more preferably in the range of 1.50 to 1.58. By setting the refractive index of the resin layer B in the above range, excellent antiglare properties can be achieved in combination with the resin layer A.
[0080] (Resin composition C) Resin composition C contains (X) a (meth)acrylate and (Y) inorganic oxide fine particles having an average particle size of 0.1 to 5 μm. The mass average molecular weight of the resin composition C is preferably 100 or more, more preferably 200 or more, and even more preferably 400 or more. On the other hand, the upper limit is preferably 500,000 or less, more preferably 400,000 or less, and even more preferably 250,000 or less.
[0081] In the present invention, when the expression "(meth)acrylate" is used, it means one or both of "acrylate" and "methacrylate". When the expression "(meth)acryloyl" is used, it means one or both of "acryloyl" and "methacryloyl". When the expression "(meth)acrylic" is used, it means one or both of "acrylic" and "methacrylic", and the same applies to other similar expressions. In addition, the (meth)acryloyl group concentration of the compound having a (meth)acryloyl group used in the present invention may be expressed as (meth)acryloyl group equivalent (g / eq). The (meth)acryloyl group equivalent is the average molecular weight per (meth)acryloyl group. For example, when a (meth)acrylate compound having a number average molecular weight of 10,000 has 10 (meth)acryloyl groups per molecule, the (meth)acryloyl group equivalent is 10,000 / 10=1,000g / eq.
[0082] ((X) (meth)acrylate) Resin composition C contains (X) (meth)acrylate. By containing (X) (meth)acrylate, the scratch resistance of the layer (resin layer) formed by curing resin composition C and its adhesion to a polyester film can be easily improved. Specific examples of (X) (meth)acrylates include those having 3 ethylenically unsaturated groups such as trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris-2-hydroxyethyl isocyanurate tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane hexa(meth)acrylate. polyfunctional (meth)acrylates having three or more functional groups; modified products of polyfunctional (meth)acrylate compounds in which a part of these (meth)acrylates is substituted with an alkyl group or ε-caprolactone; polyfunctional (meth)acrylates having a nitrogen atom-containing heterocyclic structure such as polyfunctional (meth)acrylates having an isocyanurate structure; polyfunctional (meth)acrylates having a multi-branched resin structure such as polyfunctional (meth)acrylates having a dendrimer structure and polyfunctional (meth)acrylates having a hyperbranched structure; urethane (meth)acrylates in which (meth)acrylates having hydroxyl groups, such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, etc., are added to polyisocyanates such as diisocyanates and triisocyanates, or trimers (isocyanurates) thereof. The (meth)acrylate having a hydroxyl group is preferably polyfunctional having two or more ethylenically unsaturated groups. The (X) (meth)acrylate preferably includes a urethane (meth)acrylate.
[0083] Specifically, the (meth)acrylate is preferably pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, or dipentaerythritol hexa(meth)acrylate from the viewpoint of compatibility with the (meth)acrylic polymer, and is more preferably pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, or dipentaerythritol penta(meth)acrylate from the viewpoint of scratch resistance and weather resistance of the coating film. Preferred are urethane (meth)acrylate which is a reaction product of pentaerythritol tri(meth)acrylate and hexamethylene diisocyanate, urethane (meth)acrylate which is a reaction product of pentaerythritol tri(meth)acrylate and isophorone diisocyanate, urethane (meth)acrylate which is a reaction product of dipentaerythritol penta(meth)acrylate and hexamethylene diisocyanate, and urethane (meth)acrylate which is a reaction product of dipentaerythritol penta(meth)acrylate and isophorone diisocyanate. These may be used alone or in combination of two or more.
[0084] Among the above, a trifunctional to hexafunctional polyfunctional (meth)acrylate or a urethane (meth)acrylate in which a polyfunctional (e.g., trifunctional to pentafunctional) (meth)acrylate having a hydroxyl group is added to a polyisocyanate may be used, and the above-mentioned polyfunctional (meth)acrylate and urethane (meth)acrylate may be used in combination.
[0085] The mass average molecular weight of the (X) (meth)acrylate is, for example, from 250 to 8000, preferably from 300 to 7000, more preferably from 400 to 5000, and particularly preferably from 500 to 3000. By satisfying the above range, the surface hardness of the resin layer C can be appropriately controlled. The weight average molecular weight is a value measured by gel permeation chromatography (GPC) and calculated in terms of standard polystyrene.
[0086] The (meth)acryloyl group equivalent of the (X) (meth)acrylate is, for example, preferably 80 g / eq or more and less than 150 g / eq, more preferably 85 g / eq or more and less than 135 g / eq, and even more preferably 90 g / eq or more and less than 120 g / eq. When the (meth)acryloyl group equivalent of the (X) (meth)acrylate is within the above range, the surface hardness of the resin layer C can be appropriately suppressed.
[0087] As described above, the urethane (meth)acrylate as the component (X) is a reaction product between a polyisocyanate or isocyanurate and a (meth)acrylate having a hydroxyl group, but it may be produced by reacting a polyisocyanate or isocyanurate with a mixture of a (meth)acrylate having a hydroxyl group and a (meth)acrylate not having a hydroxyl group. In this case, the (meth)acrylate not having a hydroxyl group remains as an unreacted product, but it may be included in the curable resin composition as it is and used as the component (X).
[0088] (solvent) The resin composition C may be diluted with a solvent to form a coating liquid. The resin composition C may be applied as a liquid coating liquid onto the resin layer A, and then dried and cured to form the resin layer C. Each component constituting the resin composition C may be dissolved in the solvent, or may be dispersed in the solvent. The solvent is preferably an organic solvent.Specific examples of the organic solvent include aromatic solvents such as toluene and xylene; ketone solvents such as methyl ethyl ketone (MEK), acetone, methyl isobutyl ketone (MIBK), cyclohexanone, and diisobutyl ketone; ether solvents such as diethyl ether, isopropyl ether, tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether (PGM), anisole, and phenetole; ester solvents such as ethyl acetate, butyl acetate, isopropyl acetate, and ethylene glycol diacetate; amide solvents such as dimethylformamide, diethylformamide, dimethylacetamide, and N-methylpyrrolidone; cellosolve solvents such as methyl cellosolve, ethyl cellosolve, and butyl cellosolve; alcohol solvents such as methanol, ethanol, propanol, isopropanol, and butanol; and halogen solvents such as dichloromethane and chloroform. These organic solvents may be used alone or in combination of two or more. Among these organic solvents, ester solvents, ether solvents, alcohol solvents and ketone solvents are preferably used.
[0089] The amount of the organic solvent used is not particularly limited, and is appropriately determined in consideration of the coatability of the prepared resin composition C, the viscosity and surface tension of the liquid, the compatibility of the solid content, etc. The resin composition C is prepared using the above-mentioned solvent as a coating liquid having a solid content concentration of preferably 15 to 80 mass%, more preferably 20 to 70 mass%. Note that the "solid content" in the resin composition C means the components excluding the solvent, which is a volatile component, and includes not only solid components but also semi-solid and viscous liquid substances.
[0090] (Other ingredients) The resin composition C may contain a photopolymerizable compound such as a urethane (meth)acrylate in addition to the above (meth)acrylate. Furthermore, various additives may be appropriately blended into the resin composition C as necessary within the scope of the present invention. Examples of additives that may be used in combination include photoinitiators, light stabilizers, antioxidants, antistatic agents, organic pigments, organic particles, inorganic particles, flame retardants, leveling agents, dispersants, thixotropy-imparting agents (thickeners), and defoamers.
[0091] (Photoinitiator) When the resin composition C is a photocurable resin composition, it is preferable to contain a photoinitiator in order to improve the curability. The photoinitiator is a photopolymerization initiator, and a known one can be used. Examples of the photopolymerization initiator include a photoradical generator and a photoacid generator.
[0092] Among the photopolymerization initiators that can be used in the resin composition C, examples of the photoradical generator include benzoin and its alkyl ethers, such as benzoin, benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether; acetophenone, 2,2-dimethoxy-2-phenylacetophenone [e.g., trade name "Omnirad (registered trademark) 651", manufactured by IGM RESINS], 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexyl phenyl ketone [e.g., trade name "Omnirad (registered trademark) 184", manufactured by IGM RESINS], 2-hydroxy-2-methyl-1-phenylpropan-1-one [e.g., trade name "Omnirad (registered trademark) 1173", manufactured by IGM RESINS], and the like. IGM RESINS], 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one [e.g., trade name "Omnirad® 127, IGM RESINS], 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one [e.g., trade name "Omnirad® 2959", IGM RESINS], 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one [e.g., trade name "Omnirad® 907", IGM alkylphenones such as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone; phosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide [for example, trade name "Omnirad (registered trademark) TPO", manufactured by IGM RESINS] and bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide [for example, trade name "Omnirad (registered trademark) 819", manufactured by IGM RESINS]; anthraquinones such as 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, and 2-amylanthraquinone; benzophenone and various derivatives thereof; and formic acid derivatives such as methyl benzoylformate and ethyl benzoylformate.These may be used alone or in combination of two or more.
[0093] Among these photoradical generators, from the viewpoint of the light resistance of the cured product, preferred are alkylphenones, phosphine oxides, and formic acid derivatives, more preferred are 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and methyl benzoylformate, and particularly preferred are 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one.
[0094] As the photoacid generator, known ones can be used, among which diaryliodonium salts and triarylsulfonium salts are preferred from the viewpoints of curability, acid generation efficiency, etc. Specific examples include anion salts of di(alkyl-substituted)phenyliodonium (specifically, PF6 salts, SbF5 salts, tetrakis(perfluorophenyl)borate salts, etc.). A specific example of the anion salt of (alkyl-substituted) phenyliodonium is particularly preferably a PF6 salt of dialkylphenyliodonium [trade name "Omniad (registered trademark) 250", manufactured by IGM RESINS]. These photoacid generators may be used alone or in combination of two or more.
[0095] The content of the photoinitiator is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and particularly preferably 1 part by mass or more, from the viewpoint of improving the curability, relative to a total of 100 parts by mass of the compounds having a (meth)acryloyl group in the resin composition C. On the other hand, from the viewpoint of maintaining the stability of the coating liquid when the curable resin composition C is made into a solution and from the viewpoint of the flatness of the cured coating film, the content is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and particularly preferably 5 parts by mass or less.
[0096] (Thickness) The thickness of the resin layer C is preferably 10 μm or less, more preferably in the range of 1 to 10 μm, even more preferably 1 to 8 μm, and particularly preferably in the range of 1 to 5 μm. When the thickness of the resin layer C is equal to or greater than these lower limits, the polyester film can be appropriately protected by the resin layer C. When the thickness of the resin layer C is equal to or less than these upper limits, curling and heat wrinkles can be prevented in a laminate structure having the resin layer C, such as a laminate film, and good flatness can be ensured.
[0097] (particle) It is necessary to contain (Y) inorganic oxide fine particles having an average particle size of 0.1 to 5 μm in the resin layer C. The average particle size of the inorganic oxide fine particles is preferably in the range of 0.5 to 5 μm, more preferably 1.0 to 5 μm, and even more preferably 1.5 to 4.5 μm. By satisfying the above range, it is possible to impart good antiglare properties to the laminated film of the present invention.
[0098] Examples of the inorganic oxide fine particles include alumina and silica. The content of the inorganic oxide fine particles is preferably 10 to 60 parts by mass, and more preferably 10 to 40 parts by mass, based on 100 parts by mass of the solid content of the resin composition C. When the content is 10 parts by mass or more, an effect of improving scratch resistance can be obtained. On the other hand, when the content is 60 parts by mass or less, sufficient transparency of the resin layer C can be obtained.
[0099] In order to ensure good coatability, the resin composition for forming resin layer A and resin layer C preferably has a viscosity at 25°C measured with an E-type viscometer of 10 to 60 mPa·s, and more preferably 30 mPa·s or less, more preferably 20 mPa·s or less, more preferably 15 mPa·s or less, and even more preferably 12 mPa·s or less.
[0100] <Method of forming resin layer> As described above, the resin layers A, B and C can be obtained by applying a resin composition to the surface of a polyester film, drying the composition to form a coating layer, and curing the coating layer. Examples of a method for applying the resin composition include air doctor coating, blade coating, rod coating, bar coating, knife coating, squeeze coating, impregnation coating, reverse roll coating, transfer roll coating, gravure coating, kiss roll coating, cast coating, spray coating, curtain coating, calendar coating, and extrusion coating. The drying conditions are not particularly limited, and the drying may be performed at about room temperature or by heating, for example, at about 25 to 120° C., preferably 50 to 100° C., and more preferably 60 to 90° C. The drying time is not particularly limited as long as the solvent can be sufficiently evaporated, and is, for example, about 10 seconds to 30 minutes, and preferably about 15 seconds to 10 minutes.
[0101] The method for curing the resin composition may be appropriately selected depending on the curing mechanism of the resin composition, and if the resin composition is a thermosetting resin composition, it may be cured by heating, and if it is a photocurable resin composition, it may be cured by irradiating it with energy rays. In the laminated film of the present invention, active energy rays that can be used when curing the photocurable resin composition include ultraviolet rays, electron beams, X-rays, infrared rays, and visible light. Among these active energy rays, ultraviolet rays and electron beams are preferred from the viewpoints of curability and prevention of resin deterioration.
[0102] The resin composition is preferably cured by irradiation with energy rays from the viewpoints of molding time and productivity, and of preventing thermal shrinkage and thermal deterioration of each member due to heating. The energy rays may be irradiated from either side, and may be irradiated from the polyester film side (the resin layer B side if the resin layer B has been formed) or from the opposite side of the polyester film (the resin layer A or resin layer C side if the resin layer A and / or resin layer C has been formed). When the resin composition is cured by ultraviolet irradiation in producing the laminated film of the present invention, various ultraviolet irradiation devices can be used, and as the light source, a xenon lamp, a high-pressure mercury lamp, a metal halide lamp, an LED-UV lamp, etc. can be used. The amount of ultraviolet irradiation (unit: mJ / cm 2 ) is usually 50 to 3,000 mJ / cm 2 From the viewpoints of the curability of the resin composition, the flexibility of the cured product (cured film), etc., it is preferably 100 to 1,000 mJ / cm 2 From the viewpoint of the flatness of the laminated film, it is more preferably 100 to 500 mJ / cm 2 and is appropriately determined depending on the reaction rate of the (meth)acryloyl group required in each curing step. When the composition is used in a particularly severe environment, it is preferable to increase the amount of ultraviolet light to adjust the surface hardness of the cured product of the curable resin composition.
[0103] In addition, when the resin composition is cured by electron beam irradiation during the production of the laminated film of the present invention, various electron beam irradiation devices can be used. The irradiation dose (Mrad) of the electron beam is usually 0.5 to 20 Mrad, and is preferably in the range of 1 to 15 Mrad from the viewpoints of the curability of the resin composition, the flexibility of the cured product, and prevention of damage to the substrate, but is appropriately determined depending on the reaction rate of the (meth)acryloyl group required in each curing step.
[0104] <<Physical properties of laminated film>> (Total light transmittance) When the laminated film is intended for optical use, the total light transmittance is preferably 85% or more, more preferably 86% or more, and particularly preferably 88% or more. The total light transmittance is measured using a haze meter. The details of the measurement method are described in the examples.
[0105] (Film Haze) When the laminated film is intended for optical use, the film haze is preferably 1.5% or less, more preferably 1.0% or less, and particularly preferably 0.8% or less. The film haze was measured using a haze meter. The details of the measurement method are described in the Examples.
[0106] (Average reflectance) As described above, the average reflectance of the surface of the resin layer C of the laminated film of the present invention at wavelengths of 380 to 760 nm is preferably 3.0% or less. The average reflectance was determined by using a spectrometer (V-670 manufactured by Nippon Kogaku Co., Ltd.) and the average value at wavelengths of 380 to 760 nm. The reflectance is preferably 3.0% or less, and more preferably 2.5% or less. By satisfying the above range, good antiglare properties can be obtained.
[0107] (Interference fringes I) Using a configuration of backlight (light source) / polarizer 0° / polarizer 45° / laminated film, in which the resin layer C side of the laminated film is not in contact with the 45° polarizer, the colored area when the appearance was evaluated from the resin layer C side was evaluated as a percentage (%) of the total measured area. 30% or less was judged as "Good", more than 30% to 50% or less was judged as "Good", and more than 50% was judged as "Poor". In the present invention, as described above, it is preferable that the colored area (rainbow unevenness) when the appearance was evaluated from the resin layer C side is 30% or less as a percentage of the total measured area. In addition, when the layer structure of the laminated film in the configuration for which the above appearance evaluation was performed is resin layer C / resin layer A / polyester film / resin layer B, this means that the 45° polarizing plate is attached to the resin layer B side, and on the other hand, when the layer structure of the laminated film is resin layer A / polyester film / resin layer B / resin layer C, this means that the 45° polarizing plate is attached to the resin layer A side. The same applies to the relationship between the layer structure of the laminated film and the 90° polarizing plate in the next interference fringes II.
[0108] (Interference fringes II) Using a configuration of backlight (light source) / polarizer 0° / polarizer 90° / laminated film, in which the resin layer C side of the laminated film is not in contact with the 90° polarizer, the colored area when the appearance was evaluated from the resin layer C side was evaluated as a percentage (%) of the total measured area. 50% or less was judged as "Good", more than 50% to 70% or less was judged as "Good", and more than 70% was judged as "Poor". In the present invention, as described above, it is preferable that the colored (rainbow unevenness) area when the appearance was evaluated from the resin layer C side is 50% or less as a percentage of the total measured area.
[0109] <<Characteristics and uses of laminated film>> The laminated film of the present invention has excellent antiglare properties and low optical interference properties, and further has transparency, and therefore can be used for surface protection and display surface protection. For example, the laminated film of the present invention can be suitably used as a surface protection film, particularly a surface protection film for displays, particularly a surface protection film for flexible displays, for example, a polarizer protection film used in the manufacture of polarizing plates. However, the uses of the laminated film of the present invention are not limited to these uses.
[0110] <<How to use the laminated film>> The laminate film of the present invention can be attached to a polarizer on the resin layer B side via a polyvinyl alcohol (PVA)-based adhesive layer to produce a polarizing plate. As the PVA-based adhesive, a conventionally known material can be used. As for the polarizer protective film constituting the polarizing plate, at least one of the film substrates preferably has a configuration in which the laminate film of the present invention is laminated thereto. By employing this configuration, it is possible to manufacture a polarizing plate with good visibility. The polarizing plate is also useful for image display, and image displays equipped with the polarizing plate of the present invention are also included in the scope of the present invention, and are particularly useful as vehicle-mounted image displays.
[0111] <<Explanation of terms>> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". In addition, in this specification, when it is written "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES
[0112] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the following examples in any way. The measurement and evaluation methods used in the present invention are as follows.
[0113] (1) Resin layer thickness measurement method Each laminated film was attached to a glass slide using "Aron Alpha Series" manufactured by Toa Gosei Co., Ltd., to prepare a sample for SAICS. The obtained sample for SAICS was set in a SAICS (DN-01 type manufactured by Daipla Wintes Co., Ltd.), and a cut of 300 μm wide and 1 μm deep was made in advance with a diamond cutting edge. The cut was made using a single crystal diamond blade with a V-angle dimension of 80°, a rake angle of 5°, and a relief angle of 5°. For the measurement, a Borazon cutting blade with a width of 300 μm was set on the sample with a 300 μm wide cut in advance, and the film thickness of each cured resin layer was measured at an arbitrary depth, a horizontal speed of 1 μm / s, and a vertical speed of 0.5 μm / s. A boron nitride blade with a blade width dimension of 0.3 mm, a rake angle of 20°, and a relief angle of 10° was used for the measurement. The material strength was measured from the vertical displacement position and cutting force, and the thickness of each layer was confirmed.
[0114] (2) Film haze The film haze of each laminated film was measured in accordance with JIS K 7136 using a haze meter HM-150 manufactured by Murakami Color Research Laboratory.
[0115] (3) Retardation (Re) A phase difference measuring device (KOBRA-21ADH) manufactured by Oji Scientific Instruments was used. Samples of 3.5 cm x 3.5 cm were cut out from the center of the film width direction at intervals of 10 cm in the film width direction, and the samples were placed in the device so that the angle defined by the measuring device for the film width direction was 0°. The retardation (Re) in the width direction at a wavelength of 590 nm with an incident angle of 0° was measured.
[0116] (4) Total light transmittance The total light transmittance of each laminate film was measured in accordance with JIS K 7136 using a haze meter HM-150 manufactured by Murakami Color Research Laboratory.
[0117] (5)Light transmittance The light transmittance at a wavelength of 380 nm was measured using a spectrophotometer (U-3900H, manufactured by Hitachi High-Technologies Corporation).
[0118] (6) Average reflectance A spectrometer (V-670 manufactured by Nippon Kogaku Co., Ltd.) was used, and the average value at measurement wavelengths of 380 to 760 nm was used as the average reflectance.
[0119] (7) Refractive index of resin layer To suppress reflection from the back side, black tape (Vinyl Tape VT-50, manufactured by Nichiban Co., Ltd.) was applied to the back side of the sample film beforehand. For the measurement, a spectrophotometer (UV-Visible Spectrophotometer V-670, manufactured by JASCO Corp.) was used to measure the absolute reflectance in the wavelength range of 300 to 800 nm under the following conditions: synchronous mode, incident angle 5°, N polarization, response Fast, data acquisition interval 1.0 nm, bandwidth 10 nm, and scanning speed 1000 m / min. The refractive index of the resin layer was calculated from the relationship between the data obtained from this measurement and the film thickness of the resin layer.
[0120] (8) Interference fringes I (rainbow fringes) Using a configuration of backlight (light source) / polarizer 0° / polarizer 45° / laminate film, where the resin layer C side of the laminate film was not in contact with the 45° polarizer, the appearance was evaluated from the resin layer C side, and the colored area was evaluated as a percentage (%) of the total measured area. 20% or less was rated as "Good", more than 20% to 30% or less was rated as "Good", and more than 30% was rated as "Poor".
[0121] (9) Interference fringes II (rainbow fringes) Using a configuration of backlight (light source) / polarizer 0° / polarizer 90° / laminate film, where the resin layer C side of the laminate film is not in contact with the 90° polarizer, the appearance was evaluated from the resin layer C side, and the colored area was evaluated as a percentage (%) of the total measured area. 30% or less was rated as "Good", more than 30% to 50% or less was rated as "Good", and more than 50% was rated as "Poor".
[0122] The various materials used in the examples and comparative examples were prepared as follows.
[0123] <Polyester raw materials> (PET-A) Solid-state polymerized homopolyethylene terephthalate (using Ti polymerization catalyst) (PET-B) Homopolyethylene terephthalate (using Sb polymerization catalyst) (PET-C) Masterbatch made by blending homopolyethylene terephthalate (using Ti polymerization catalyst) with 5% by mass of silica particles with an average particle size of 2.3 μm. (PET-D) Masterbatch containing homopolyethylene terephthalate (using Sb polymerization catalyst) and 10% by mass of UV absorber (Cyasorb 3638F, manufactured by Sun Chemical Co.)
[0124] <PETフィルム> The raw material for the outermost layer (surface layer) was a mixture of PET-A at a ratio of 94% by mass and PET-C at a ratio of 6% by mass, and the raw material for the intermediate layer was a mixture of PET-B at a ratio of 75% by mass and PET-D at a ratio of 25% by mass. The raw materials were fed to two extruders, melted at 285°C, and then co-extruded onto a cooling roll set at 40°C in a layer structure of two types and three layers (surface layer / intermediate layer / surface layer = discharge amount (mass ratio) of 4 / 92 / 4), and cooled and solidified to obtain an unstretched sheet. Next, the film was stretched 3.6 times in the longitudinal direction at a film temperature of 85°C using the roll peripheral speed difference, and then the coating liquid of the following resin composition A and B was applied to both sides of one side of this longitudinally stretched film, introduced into a tenter, stretched 3.9 times in the transverse direction at 110°C, and heat-treated at 210°C, and the thickness was 75 μm and the film thickness (after drying) was 25 g / m 2 Resin layer A and film thickness (after drying) are 45 g / m 2 A master roll of a laminated polyester film (film width: 3200 mm) having the resin layer B was obtained.
[0125] <Resin composition> (Resin Composition A) The following compounds were mixed in a ratio of A1:A2:B1:C2=30:35:15:20 (mass % of solid content).
[0126] (Resin composition B) The following compounds were mixed in a ratio of A1:B2:C1=60:35:5 (mass % of solid content). ((Binder resin)) (A1) Aqueous dispersion of polyester resin copolymerized with the following composition Monomer composition: (acid component) terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / / (diol component) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (mol%) (A2) A water dispersion of a polyester resin having a condensed polycyclic aromatic ring copolymerized in the following composition: Monomer composition: (acid component) 2,6-naphthalenedicarboxylic acid / 5-sodium sulfoisophthalic acid / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%) ((Crosslinking Agent)) (B1) Hexamethoxymethylol melamine (B2) Polyglycerol polyglycidyl ether, an epoxy compound ((particle)) (C1) Silica particles with an average particle size of 70 nm (C2) Zirconia sol with an average particle size of 20 nm
[0127] [Example 1] The above PET film was previously slit into a roll film with a width of 1600 mm, and a sample cut to A4 size was prepared by coating the resin layer A with a bar coater (#6) so that the resin composition C prepared as described below was applied to the sample so that the coating thickness (after drying) was 4 μm. After drying by heating at 90° C. for 1 min, the sample was exposed to an accumulated light dose of 400 mJ / cm 2 . 2 The resin layer C was cured by irradiation with ultraviolet light in a nitrogen atmosphere, to obtain a laminated film having a laminated structure of resin layer B / polyester film / resin layer A / resin layer C.
[0128] (Resin layer composition C) To 40 parts by mass of pentaerythritol triacrylate, 10 parts by mass of a roughening agent (manufactured by Fuji Silysia Chemical Co., Ltd.: Sylysia 730, average particle size: 4.0 μm), 91 parts by mass of a refractive index control agent (manufactured by Nippon Shokubai Co., Ltd.: Zircostar ZP-153, zirconium oxide MEK solution), 2 parts by mass of a photopolymerization initiator (manufactured by IGM Resins BV: Omnirad127), 1 part by mass of a dispersant (2-hydroxyethyl methacrylate acid phosphate), and 142 parts by mass of MEK (methyl ethyl ketone) were added to prepare a resin composition C. The refractive index of the resin layer C was 1.65.
[0129] [Example 2] A laminated film was obtained by producing in the same manner as in Example 1, except that the PET film (A4 cut size sample) was taken from the opposite end of the rolled film.
[0130] [Comparative Example 1] Example 2 was carried out in the same manner as in Example 1, except that resin layer C was provided on resin layer B of the PET film, to obtain a laminated film.
[0131] <Evaluation Results> The properties of each of the laminated films obtained in the above Examples and Comparative Examples are shown in Table 1 below.
[0132] [Table 1]
[0133] <Consideration> From the results of the above examples and comparative examples, it was found that a polyester film having a structure in which resin layer A and resin layer C are sequentially laminated on the surface of the polyester film, and resin layer A contains a compound having a condensed polycyclic aromatic structure, thereby making it possible to achieve both low reflectivity and low optical interference (suppression of the occurrence of interference fringes). In contrast, it was also found that Comparative Example 1, in which resin layer C was provided on resin layer B, had inferior reflection characteristics. The cause of such a difference is presumably due to the large difference in refractive index between resin layer A and resin layer C. In addition, the composition of resin layer A reduces optical interference with resin layer C, making interference fringes less visible. On the other hand, by adopting the configuration of resin layer C, it is possible to obtain the desired antiglare properties.
[0134] It was also found that by adjusting the thickness and composition of each of resin layers A, B and C, such as the particle size and content, it is possible to achieve both low reflection characteristics (anti-glare properties) and low optical interference (suppression of the occurrence of interference fringes). [Industrial Applicability]
[0135] The laminated film of the present invention has low reflection properties (anti-glare properties) at a high level while also achieving low optical interference (suppression of interference fringes). Among these, it can be suitably used for optical applications such as display members (surface protection films, etc.) that require flexibility. Therefore, for example, when used as a polarizer protective film for producing polarizing plates, a laminate film can be provided that does not generate interference colors due to optical interference under polarized light, and yet has low reflectance and good anti-glare properties, and the industrial value of the present invention is high. [Explanation of symbols]
[0136] 1. Laminated film 2 Resin layer B 3. Polyester film 4 Resin layer A 5 Resin layer C
Claims
1. A laminated film having a structure in which a resin layer A and a resin layer C are laminated in this order on one surface of a polyester film, and a resin layer B is laminated on the opposite surface, the polyester film has a retardation (Re) of less than 3000 nm, the resin layer A is a cured product of a resin composition A containing (a) a binder, (b) a crosslinking agent, and (c) particles, the resin layer C is a cured product of a resin composition C containing (X) a (meth)acrylate and (Y) inorganic oxide fine particles having an average particle size of 0.1 to 5 μm, and the (a) binder contains a compound having a condensed polycyclic aromatic structure.
2. 2. The laminate film according to claim 1, wherein the average reflectance of the surface of the resin layer C at a wavelength of 380 to 760 nm is 3.0% or less.
3. The laminate film according to claim 1 , wherein the compound having a condensed polycyclic aromatic structure is a polycyclic polyester resin.
4. 2. The laminated film according to claim 1, having a film haze of 1.5% or less.
5. The laminate film of claim 1 , wherein the polyester film comprises an ultraviolet absorbing agent.
6. 2. The laminate film according to claim 1, wherein the polyester film is a polyethylene terephthalate (PET) film.
7. The laminate film according to claim 1, wherein the refractive index difference (nx-ny) of the polyester film is 0.04 or less.
8. The laminated film according to claim 1, wherein the polyester film has a thickness of 9 to 125 μm.
9. The laminate film according to claim 1, wherein the resin layer A has a thickness of 10 to 60 nm.
10. The laminate film according to claim 1, wherein the resin layer B has a thickness of 20 to 100 nm.
11. The laminated film according to claim 1 , wherein the resin layer C has a thickness of 10 μm or less.
12. The laminate film according to any one of claims 1 to 11, wherein the laminate film has a structure of backlight (light source) / polarizing plate 0° / polarizing plate 45° / laminate film, and the resin layer C side of the laminate film is not in contact with the polarizing plate 45°. When the appearance is evaluated from the resin layer C side, the area of coloring (rainbow unevenness) is 30% or less of the entire measured area.
13. The laminate film according to any one of claims 1 to 11, wherein the laminate film has a structure of backlight (light source) / polarizing plate 0° / polarizing plate 90° / laminate film, and the resin layer C side of the laminate film is not in contact with the 90° polarizing plate, and the area of coloring (rainbow unevenness) when the appearance is evaluated from the resin layer C side using the structure is 50% or less of the entire measured area.
14. The method for producing a laminated film according to any one of claims 1 to 11, comprising: a production step 1 in which a film is stretched in the longitudinal direction by 3.0 to 4.0 times, and then a coating solution of resin composition A and resin composition B is applied to both sides of one side of the longitudinally stretched film, the film is introduced into a tenter, stretched in the transverse direction by 3.6 to 6.0 times, and heat-treated at 215°C or less to obtain a laminated polyester film having a resin layer A on one side and a resin layer B on the other side; and a production step 2 in which a resin composition C is applied to the resin layer A side of the laminated polyester film and dried.
15. The laminate film according to any one of claims 1 to 11, which is used for surface protection.
16. The laminate film according to any one of claims 1 to 11, which is used for protecting a display surface.
17. The laminate film according to any one of claims 1 to 11, which is used for protecting a polarizer.
18. A polarizing plate comprising the resin layer B of the laminate film according to any one of claims 1 to 11 attached to one side of a polarizer.
19. An image display comprising the polarizing plate according to claim 18.
20. The image display device according to claim 19, which is mounted on a vehicle.
Citation Information
Patent Citations
Polyester film for polarizing plate-protection
JP2013200435A
Polarizing plate and liquid crystal display device
JP2013200578A